Heavy-Duty Vehicle Braking Stability Control and HIL Verification for Improving Traffic Safety - Fahui Wang; Yongjie Lu; Haoyu Li (Journal of Advanced Transportation)
The braking failure of heavy vehicles under long downhill or curved conditions may cause traffic crash and reduce road traffic efficiency. Therefore, to improve the traffic safety and braking stability of vehicles under special road conditions, a braking dynamic model and control system based on the interval uncertainty analysis are proposed, and the safety of the active control model is verified by experiments (HIL). Firstly, the interval uncertain dynamic model is established based on the Monte Carlo method, and the braking failure simulation analysis of the right front wheel of heavy vehicles is carried out in the set of three uncertain intervals. Secondly, the fuzzy PID and sliding mode controller based on yaw and centroid error are designed to find the optimal control strategy from the two kinds of control strategies for HIL experiments. Finally, the actual control effect and feasibility of these control algorithms for heavy vehicle braking under special road conditions are verified by HIL experiments. The experimental results show that under the action of the fuzzy PID control strategy, the running stability of the vehicle is significantly improved compared with no control, which effectively reduces the risk of vehicle braking failure and improves the active safety and stability of the vehicle.